GLOBE practices and values: A case of diminishing marginal utility? - Brewer, Paul; Venaik, Sunil (Journal of International Business Studies, 2010)
The GLOBE study of national cultures identified nine dimensions of culture. These nine dimensions were measured in the form of societal practices (as things are) and societal values (as things should be). The correlations between practices and values for societies, surprisingly, were found to be significantly negative for seven dimensions. Apparently, people's values are contrary to their practices. A note, which appeared in a recent issue of this journal, proposes that these anomalous correlations result from diminishing marginal utility. The note argues that marginal utility theory applies to cultural dimensions, and that the GLOBE values measure societies’ marginal preferences for most of the dimensions, rather than total preference weights. Through close analysis of the questionnaire items used by the GLOBE team, we show that this is not the case. We demonstrate that the GLOBE questions, as asked, do not elicit marginal preferences. In fact they elicit values, as claimed by GLOBE, but recognizing that values may well be shaped, in part, by existing practices. We call for further study into the GLOBE scores, as it is likely that different explanations apply to practices/values relationships across different dimensions.